EKSISTENSI MULTIPARTAI DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA - Else Suhaimi (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
Representative democracy in Indonesia is a democracy mandated in the Constitution and Pancasila. The manifestation of democracy through a general election conducted every five years with the aim to elect members of the parliament at the central and regional levels. Members of the parliament are candidates promoted by political parties. In the history of partying in Indonesia it is seen that the party system is built based on multiparty. Party system with multiparty in the old order era has managed to build a political party ideology so as to emerge political parties that berideologi. In the new order era ideologipartai-political parties in the